Epidemiology of atherosclerotic cardiovascular disease in polygenic hypercholesterolemia with or without high lipoprotein(a) levels - Vinci, Pierandrea; Fiotti, Nicola; Panizon, Emiliano; Tosoni, Letizia Maria; Cerrato, Carla; Pellicori, Federica; Pirulli, Alessia; Altamura, Nicola; Schincariol, Paolo; Di Girolamo, Filippo Giorgio; Biolo, Gianni (Frontiers in Cardiovascular Medicine, 2024)
Background and aims Epidemiology of atherosclerotic cardiovascular disease might be different in patients with polygenic hypercholesterolemia plus high levels (≥30 mg/dl) of Lp(a) (H-Lpa) than in those with polygenic hypercholesterolemia alone (H-LDL). We compared the incidence of peripheral artery disease (PAD), coronary artery disease (CAD), and cerebrovascular disease (CVD) in patients with H-Lpa and in those with H-LDL. Methods Retrospective analysis of demographics, risk factors, vascular events, therapy, and lipid profile in outpatient clinical data. Inclusion criteria was adult age, diagnosis of polygenic hypercholesterolemia, and both indication and availability for Lp(a) measurement. Results Medical records of 258 patients with H-Lpa and 290 H-LDL were reviewed for occurrence of vascular events. The median duration of follow-up was 10 years (IQR 3–16). In spite of a similar reduction of LDL cholesterol, vascular events occurred more frequently, and approximately 7 years earlier (P = 0.024) in patients with H-Lpa than in H-LDL (HR 1.96 1.21–3.17, P = 0.006). The difference was around 10 years for acute events (TIA, Stroke, acute coronary events) and one year for chronic ones (P = 0.023 and 0.525, respectively). Occurrence of acute CAD was higher in H-Lpa men (HR 3.1, 95% CI 1.2–7.9, P = 0.007) while, among women, PAD was observed exclusively in H-Lpa subjects with smoking habits (P = 0.009). Conclusions Patients with high Lp(a) levels suffer from a larger and earlier burden of the disease compared to those with polygenic hypercholesterolemia alone. These patients are at higher risk of CAD if they are men, and of PAD if they are women.